2019
DOI: 10.1002/mgg3.717
|View full text |Cite
|
Sign up to set email alerts
|

Influence of glutathione S‐transferases (GSTM1, GSTT1, and GSTP1) genetic polymorphisms and smoking on susceptibility risk of chronic myeloid leukemia and treatment response

Abstract: Background Glutathione S‐transferases (GSTs) polymorphisms may impact on chronic myeloid leukemia (CML) risk or heterogeneous responses to Imatinib mesylate (IM). The aim of this study was to evaluate the correlation between GSTs polymorphisms and CML risk, treatment response. Methods We genotyped GSTM1, GSTT1 null deletion polymorphisms, and GSTP1 Ile105Val polymorphism by PCR methods and BCR‐ABL transcripts were analyzed by qRT‐PCR in 104 CML patients and 104 sex‐ and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 28 publications
5
21
2
Order By: Relevance
“…Such cancers include lung cancer (Mir Muhammad NasirUddin, 2014), ovarian cancer (Coughlin and Hall, 2002) and breast cancer (Hashemi et al, 2012). Previous studies have reported about GSTs association with heamatological malignancy, but with conflicting findings as mentioned previously (Dunna et al, 2012;Zhou et al, 2013;Rostami internal positive control.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Such cancers include lung cancer (Mir Muhammad NasirUddin, 2014), ovarian cancer (Coughlin and Hall, 2002) and breast cancer (Hashemi et al, 2012). Previous studies have reported about GSTs association with heamatological malignancy, but with conflicting findings as mentioned previously (Dunna et al, 2012;Zhou et al, 2013;Rostami internal positive control.…”
Section: Discussionmentioning
confidence: 99%
“…Some genes of cytosolic enzymes play a crucial role in the detoxification of activated carcinogens and implications in cancer progress, particularly GSTP1, GSTM1, and GST1 (Sailaja et al, 2010). Polymorphisms in these genes lead to the absence or decreased detoxification ability of enzymes, their dysfunction, and finally may impact on the risk of cancer development and heterogeneous drug responsiveness Editorial Process: Submission:10/06/2019 Acceptance:01/10/2020 (Rostami et al, 2019).…”
Section: Genetic Polymorphism Of Gstp1 Gstm1 and Gstt1 Genes And Susmentioning
confidence: 99%
See 2 more Smart Citations
“…24 Among GST genes, GSTM1, GSTT1, and GSTP1 have well-defined single nucleotide polymorphisms (SNPs). 25 The GSTT1 gene contains two alleles, the functional gene GSTT1+ and the nonfunctional gene GSTT1null. Similarly, the GSTM1 gene contains the functional gene GSTM1+ and the nonfunctional gene GSTM1null.…”
Section: Introductionmentioning
confidence: 99%